Bortezomib with high dose melphalan conditioning for autologous transplant is safe and effective in patients with heavily pretreated and high risk multiple myeloma. Issue 7 (July 2013) - Wong Doo, Nicole; Thompson, Philip A.; Prince, H. Miles; Seymour, John F.; Ritchie, David; Stokes, Kerrie; Burbury, Kate; Wolf, Max; Joyce, Trish; Harrison, Simon J.
Abstract: There are no uniform guidelines for the treatment of relapsed refractory multiple myeloma (MM), however autologous stem cell transplant (SCT) remains an important treatment modality. Although a number of modifications to high dose melphalan (HDM) conditioning have been evaluated, improvement in overall survival has not been demonstrated. We now report our experience of 23 patients with heavily pretreated MM (median lines of prior treatment 3 [range 1–6]) who underwent SCT with bortezomib and high dose melphalan (BorHDM). The overall response rate (at least partial response [PR]) was 65.4%. Median overall survival (OS) was 24 months. A subset of patients who relapsed ≤ 12 months after initial SCT had significantly longer OS after BorHDM SCT compared to a historical control group who received HDM conditioning alone (14.5 vs. 8 months, respectively, p = 0.011). In summary, BorHDM SCT produces very good response rates in heavily pretreated MM, and may increase survival in the salvage setting in patients who relapse early after initial SCT. We propose that its use should be explored as part of a tandem approach in patients undergoing initial SCT who are at high risk of early relapse.